Paraquat Degradation From Contaminated Environments: Current Achievements and Perspectives - Huang, Yaohua; Zhan, Hui; Bhatt, Pankaj; Chen, Shaohua (Frontiers in Microbiology, 2019)
Paraquat herbicide has served over five decades to control annual and perennial weeds. Despite agricultural benefits, its toxicity to terrestrial and aquatic environments raises serious concerns. Paraquat cannot rapidly degrade in the environment and is adsorbed in clay lattices that require urgent environmental remediation. Advanced oxidation processes (AOPs) and bioaugmentation techniques have been developed for this purpose. Among various techniques, bioremediation is a cost-effective and eco-friendly approach for pesticide-polluted soils. Though several paraquat-degrading microorganisms have been isolated and characterized, studies about degradation pathways, related functional enzymes and genes are indispensable. This review encircles paraquat removal from contaminated environments through adsorption, photocatalyst degradation, AOPs and microbial degradation. To provide in-depth knowledge, the potential role of paraquat degrading microorganisms in contaminated environments is described as well.